Serbia and Montenegro : Poverty Assessment, Volume 1. Executive Summary - World Bank (Washington, DC, 2013)
This Poverty Assessment is the first output of a multi-year program adopted by the World Bank to assist the Governments of Serbia and Montenegro in the development and implementation of their Poverty Reduction Strategies. The program relies on collaboration in joint data production and analysis. Based on data collected in 2002, the report finds that absolute material poverty affects every tenth person in both Serbia and Montenegro. From an historical standpoint, this is a very high incidence. Inequality remained moderate by regional standards, and as a result poverty is shallow. At the same time vulnerability--or exposure to negative shocks and inability to cope with them-- threatens many currently non-poor individuals. At least as many suffer from deprivation in other dimensions of well being, such as health, education, housing, social inclusion or property rights. Material poverty, therefore, is not the only challenge for the Governments. Four factors are most strongly related to poverty: low education attainment; joblessness; the location in rural areas and depressed regions, and the presence of socially disadvantaged members (such as internally displaced persons or Roma). The poor are found to face serious problems of access to public services (health, education, sanitation) and suffer disproportionately from the deterioration in the quality of public service provision. Even though some of the social assistance programs are among the best targeted programs in the region, the social protection system as a whole suffers from large exclusion errors. Given the high level of vulnerability of the population and the shallowness of poverty, a broad-based growth strategy that ensures that the benefits accrue at least proportionately to the poor is central for accelerated poverty reduction. Improvements in the business climate will stimulate private sector growth and feed into employment generation. Growth will increase fiscal revenues to remedy the problems of chronic under funding, while structural and public administration reforms will strengthen the governance and the quality of services provided to the poor. The multidimensional nature of poverty requires concerted and well coordinated action in different sectors. The report is organized in two volumes. Volume One (Executive summary) summarizes the Report content. Volume Two (Main report) provides detailed results of poverty analysis. Due to data limitations the sectoral part of the main report covers Serbia in greater details. An analysis of available data for Montenegro is presented in a background paper.